Practical applications in sports nutrition - Fink, Heather Hedrick; Mikesky, Alan E. (Jones & Bartlett Learning, 2018)
Revised and updated with a full-color design and art program, the Fifth Edition of Practical Applications in Sports Nutrition provides students and practitioners with the latest sports nutrition information and dietary practices so they can assist athletes and fitness enthusiasts in achieving their personal performance goals. With data and statistics from the latest nutrition research and guidelines, it demonstrates effective ways to communicate sports nutrition messages to athletes and how to motivate individuals to make permanent behavior change.